1994
DOI: 10.1016/0020-7292(94)90301-8
|View full text |Cite
|
Sign up to set email alerts
|

Screening for consumptive coagulopathy in preeclampsia

Abstract: A combination of platelet count and APTT is probably a practical and cost-effective combination to screen for consumptive coagulopathy in PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…The super-hypercoagulable state of PE may also lead to disorder of metabolism as well as multiple organ dysfunction and may even complicate maternal and fetal lives. Therefore, coagulation testing is common in these patients for evidence of DIC [19,20] and HELLP (hemolysis, enzyme elevation and low platelet) syndrome). Thus, The study aimed to investigate changes in some coagulation parameters in a group of Sudanese pregnant women with PE and compared them with normal pregnancies.…”
mentioning
confidence: 99%
“…The super-hypercoagulable state of PE may also lead to disorder of metabolism as well as multiple organ dysfunction and may even complicate maternal and fetal lives. Therefore, coagulation testing is common in these patients for evidence of DIC [19,20] and HELLP (hemolysis, enzyme elevation and low platelet) syndrome). Thus, The study aimed to investigate changes in some coagulation parameters in a group of Sudanese pregnant women with PE and compared them with normal pregnancies.…”
mentioning
confidence: 99%
“…Platelet counts of less than 100,000/µL in women with preeclampsia may be associated with an impaired coagulation function and should prompt additional investigations of the coagulation status (12). Instead of stratifying patients according to platelet count as a trigger to order coagulation tests, some recommend that it is practical and cost-effective to screen for both platelet count and coagulation studies at the same time (14,15). As reflected from the current survey findings, a significant proportion of anesthesiologists in Turkey still prefer general anesthesia regardless of a normal coagulation profile and a platelet count exceeding 100,000/µL.…”
Section: Discussionmentioning
confidence: 99%
“…Using the PUBMED database, a literature search (search date November 12, 2007) with the search terms, intrauterine fetal death, coagulopathy, bleeding, hemorrhage, and delivery complications, yielded eight studies. [15][16][17][18][19][20][21][22] Only one of these studies described coagulopathy associated with IUFD, citing a prevalence of 11%. 15 To further clarify the prevalence and clinical presentation of coagulopathy in women with labor induction after IUFD, we performed a retrospective cohort study and identified the percentage of women with IUFD who experienced a clinically relevant coagulation problem during or after delivery.…”
Section: Introductionmentioning
confidence: 99%